Analysis of delays in the stages of breast cancer care at the University Clinics of Kinshasa - Limanga, Stephan B.; Ebola, Francis; Ibanda, Blanchard T.; Ombha, Ernest L.; Ingala, Pierre Joseph A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: The DRC faces the paradox of high mortality and low incidence of breast cancer due to late consultations and delayed treatment; however, it lacks studies detailing the different delays of breast cancer management. We initiated this study to assess these delays and identify the associated factors. Methods: This was a cross-sectional study conducted on 201 records of women followed for breast cancer at the University Clinics of Kinshasa (UCK) from January 2020 to December 2024. Population characteristics and delays were described using descriptive statistics, logistic regression was used to identify factors associated with delays. Results: The mean age was 48±12 years. 90.8% of patients were diagnosed at advanced stages, 67% received chemotherapy as first treatment. The median patient delay was 365 days, the median diagnostic delay was 26 days, the median treatment delay was 39 days, the median health system delay was 67 days, the median total delay was 398 days. Single women had a higher risk of consultation delay (aOR=2.48; p=0.02), diagnostic delay (aOR=1.79 p=0.01) and treatment delay (aOR=3.67; p=0.04). Women who followed alternative pathways had a higher risk of delay in consultation (aOR=9; p=0.01), diagnosis (aOR=3.27; p=0.02), and treatment (aOR=3.27; p=0.01). Consulting for symptoms other than breast lump was associated with a higher risk of treatment delay (aOR=3.44; p=0.02). Conclusions: Efforts must be made to address the causes of delayed consultations and to improve the patient care pathway.